Respon Genotipe Padi Gogo terhadap Defisiensi P - Tasliah, Tasliah; Suhartini, Tintin; Prasetiyono, Joko; Somantri, Ida Hanarida; Bustamam, Masdiar (Jurnal Penelitian Pertanian Tanaman Pangan, 2011)
Insufficient P is a limiting factor for rice production. Tolerant varieties to deficiency P are very important to solve the problem. The objective of the experiment was to evaluate rice genotypes to P deficiency and its interaction to Al toxicity. The experiment was conducted at the green house of ICABIOGRAD (Indonesian Center for Agricultural Biotechnology and Genetic Resources Research and Development) in WS 2006, using Yoshida solution. Molecular analysis was conducted in 2010 to observe the effectiveness of gene Pup1 segment in upland rice varieties to be compared with Kasalath tolerance variety from India. Plastic box of 10 ltr, containing solution as media was used in the experiment. The treatments were arranged in a split-split plot design with three replications. Treatments were two levels of Aluminum (0 and 45 ppm Al) as a main plot, and 4 levels application of P fertilizer (0, 0.5, 5.0, and 10 ppm P) as sub plots, and sixteen upland rice genotypes as sub-sub plots. Results showed that there were interactions between P, Al treatments and genotypes to characters which were observed. Application of P up to 10 ppm P increased plant height, number of tillers, shoot dry weight, and root dry weight significantly, but not for root length. The effects of aluminum were decreasing in plant height, shoot and root dry weight and root length significantly, but not for number of tillers. Evaluation of tiller number for P deficiency treatment showed three cultivars were tolerant to P deficiency, namely: Way Rarem, Limboto and Sentani, and five genotypes were moderately tolerant: Way Rarem, Jatiluhur, Sentani, K36-5-1-1, Limboto, dan NIL-C443. Genotypes indicated tolerant to both Al toxicity and P deficiency, were Way Rarem, Jatiluhur, Sentani, K36-5-1-1, Limboto, dan NIL-C443. There were no correlation between rice tolerance to P deficiency with rice tolerance to aluminum toxicity. Molecular analysis using Pup1 specifik primers showed fully Pup1 segment on NIL-C443, K36-5-1-1, Jatiluhur, Limboto, Silugonggo, Way Rarem and those genotypes showed tolerance or moderately a tolerant to P deficiency, except for Silugonggo.